THE INFLUENCE OF PRICE, QUALITY AND COFFEE SERVICE AT SUMBERJAYA COFFEE SHOP - Milana, Lia; aditya sanjaya, Rizky (Universitas Majalengka, 2024)
This study aims to examine the effect of price, quality and service variables on customer satisfaction in Sumberjaya coffee shops. This research uses a survey-based quantitative approach involving 30 respondents selected using purposive sampling method. Primary data was obtained through an open-ended questionnaire that had been tested for validity and reliability to ensure the accuracy and consistency of the measuring instrument. Data processing was carried out using multiple linear regression analysis to evaluate the relationship between the independent variables of price, quality and service with the dependent variable of customer satisfaction. The results showed that all items in the questionnaire were valid and the research instrument was reliable. Statistically, the variables, price, and service have a significant effect on customer satisfaction, both individually and simultaneously. The findings provide practical implications for coffee shop managers in Sumberjaya to focus on improving these three elements to increase overall customer satisfaction.